Skończone Odkształcenia Obrotowo-Symetrycznych Powłok w Stanie Błonowym Przy Pewnych Typach Fizycznej Nieliniowości - Orkisz, J. (Engineering Transactions, 1965)
This paper is devoted to the problem of finite deformation of flexible axially-symmetric shells in a membrane state of stress in the case of physical nonlinearity of certain types. The pbysical relations used in the present paper follow from the Nádai-Davis equations. As a result we obtain sets of differential equations describing the behaviour of the shells when both if principal stresses 01 and o2 ale positive and in the «zone of folds», in which the circum-integrated numerically by the Adams method in two differential stress 02 = 0. These equations are integrated numerically by particular cases of a plane membrane and 2 conical shell of variable thickness, The present paper presents some generalization of the works of A, S. GRIGOREV [10, 11] from the viewpoint of the physical type of the body, the existence of tangential load and the variability of the wall thickness in the undefoimed state.